2020
DOI: 10.1111/pirs.12506
|View full text |Cite
|
Sign up to set email alerts
|

The variegated role of proximities in acquisitions by domestic and international companies in different phases of economic cycles

Abstract: This paper aims at an understanding of acquisition processes in a strongly industrialized and export-oriented economy in Central Europe. Drawing on a proximity framework and behaviour theory, the paper investigates that the geographical proximity dimension is more influential than the cognitive proximity dimension. At the same time, cognitive proximity matters more for foreign firms investing into the economy than for domestic acquisitions. While the role of cognitive proximity diminished during the economic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…There is a consensus that corporations, especially acquirers, engage in M&A events out of motivations such as financial enticements [24,43], market expansion [18], and access to scarce resources and localized assets [13,29]. Certainly, the specific pursuits related to M&A activities would differ across individual corporations with various sizes, industrial attributes, and ownership structures [32,44,45]. Some studies on M&As have uncovered the preferences of acquisition target selection carried out by corporations with different attributes [44,46].…”
Section: Corporate Heterogeneities Of Manda Activitiesmentioning
confidence: 99%
See 4 more Smart Citations
“…There is a consensus that corporations, especially acquirers, engage in M&A events out of motivations such as financial enticements [24,43], market expansion [18], and access to scarce resources and localized assets [13,29]. Certainly, the specific pursuits related to M&A activities would differ across individual corporations with various sizes, industrial attributes, and ownership structures [32,44,45]. Some studies on M&As have uncovered the preferences of acquisition target selection carried out by corporations with different attributes [44,46].…”
Section: Corporate Heterogeneities Of Manda Activitiesmentioning
confidence: 99%
“…With few exceptions [21,34,47], research on the spatial merger behaviors and acquiring predilections of service firms, as well as the relevant differences between manufacturing and services, is relatively limited. Existing studies have also indicated that the acquiring preferences would vary across corporations with different ownership structures (e.g., domestic and foreignowned) [32,42]. Multinational enterprises (MNEs) frequently execute partial acquisitions rather than full acquisitions to reduce their liability of foreignness and to maintain an effective local partner [46].…”
Section: Corporate Heterogeneities Of Manda Activitiesmentioning
confidence: 99%
See 3 more Smart Citations